Involvement of lysophosphatidic acid–induced astrocyte activation underlying the maintenance of partial sciatic nerve injury–induced neuropathic pain. Issue 11 (November 2018) - Ueda, Hiroshi; Neyama, Hiroyuki; Nagai, Jun; Matsushita, Yosuke; Tsukahara, Tamotsu; Tsukahara, Ryoko
Abstract : Abstract: We have previously demonstrated that lysophosphatidic acid (LPA) plays key roles in the initial mechanisms for neuropathic pain (NeuP) development. Here, we examined whether LPA receptor mechanisms and LPA production are related to the glial activation at a late stage after partial sciatic nerve ligation (pSNL) by use of microglial inhibitor, Mac1-saporin or astrocyte inhibitor, and L-α-aminoadipate (L-AA). Although single intrathecal injection of LPA1/3 antagonist, Ki-16425 did not affect the pain threshold at day 7 after the spinal cord injury, repeated treatments of each compound gradually reversed the basal pain threshold to the control level. The intrathecal administration of a microglia inhibitor, Mac-1-saporin reversed the late hyperalgesia and LPA production at day 14 after the pSNL, whereas L-AA inhibited the hyperalgesia, but had no effect on LPA production. The involvement of LPA receptors in astrocyte activation in vivo was evidenced by the findings that Ki-16425 treatments abolished the upregulation of CXCL1 in activated astrocytes in the spinal dorsal horn of mice at day 14 after the pSNL, and that Ki-16425 reversed the LPA-induced upregulation of several chemokine gene expressions in primary cultured astrocytes. Finally, we found that significant hyperalgesia was observed with intrathecal administration of primary cultured astrocytes, which had been stimulated by LPA in a Ki-16425–reversible manner. All these findings suggest that LPA production and LPA1/3 receptor activation through differential glial mechanisms play key roles in the maintenance as well as initiation mechanisms in NeuP. Abstract : This study describes a mechanism underlying the maintenance of neuropathic pain through lysophosphatidic acid production and actions, which are mediated differentially by microglia and astrocytes.